Soloist folio for french horn (in F) or Eb alto horn (mellophone) with piano accompaniment - WEBER, C.M. Von [et.al] (Rubank Inc., 1919)
Adagio from der freischutz...von webernAndante from concerto op. 64 ..........MendelssohnnAndante from fifth symphony..........TschaikowskynBohemian girl melodies....BAlfenCavatina from stradella....flotow